Integrated Phosphoproteome and Transcriptome Analysis Reveals Chlamydia-Induced Epithelial-to-Mesenchymal Transition in Host Cells - Piotr K. Zadora (Cell Reports, 2019)
Summary: Chlamydia trachomatis (Ctr) causes a range of infectious diseases and is epidemiologically associated with cervical and ovarian cancers. To obtain a panoramic view of Ctr-induced signaling, we performed global phosphoproteomic and transcriptomic analyses. We identified numerous Ctr phosphoproteins and Ctr-regulated host phosphoproteins. Bioinformatics analysis revealed that these proteins were predominantly related to transcription regulation, cellular growth, proliferation, and cytoskeleton organization. In silico kinase substrate motif analysis revealed that MAPK and CDK were the most overrepresented upstream kinases for upregulated phosphosites. Several of the regulated host phosphoproteins were transcription factors, including ETS1 and ERF, that are downstream targets of MAPK. Functional analysis of phosphoproteome and transcriptome data confirmed their involvement in epithelial-to-mesenchymal transition (EMT), a phenotype that was validated in infected cells, along with the essential role of ERK1/2, ETS1, and ERF for Ctr replication. Our data reveal the extent of Ctr-induced signaling and provide insights into its pro-carcinogenic potential. : Zadora et al. performed an integrated global phosphoproteomic and transcriptomic analysis, revealing a comprehensive map of Chlamydia-induced host cell signaling and identifying transcription factors ETS1 and ERF, which drive epithelial-to-mesenchymal transition. These insights provide mechanistic clues to Chlamydia pathogenesis and serve as an important resource for future studies. Keywords: Chlamydia trachomatis, signaling, human papillomavirus, transcription factors, cervical cancer, ovarian cancer, human primary cells